Knowledge-Based Fast Web Query Engine using NoSQL - Cooper, Peter A.; Omar, Blimat Ahmed (Ieee, 2018)
In this paper, we describe a new search interface that offers effective, domain-independent, knowledge-based information retrieval allowing users to expand queries automatically and guide users as they evolve their queries interactively. Although search engines are very useful for obtaining information from the World Wide Web, users still have problems obtaining the most relevant information when processing their web queries. Prior research has attempted to use different types of methods to improve web querying processing with various levels of success. Here we use NoSQL for fast web query searching because it has many advantages and benefits of using NoSQL i.e. time efficiency, Retrieving data from the huge amount of data. An analysis of different queries from different application domains using the semantic and linguistic knowledge illustrates how more relevant results can be obtained.
6th International Symposium on Digital Forensic and Security (ISDFS) -- MAR 22-25, 2018 -- Antalya, TURKEY
Keywords: NoSQL; Web query searching; Categorize the data; Retrieving the data